Curbing Elitist Populism in Indonesia's Lawmaking: A Constitutional Law Perspective - Zulkarnain Ridlwan; Budiyono Budiyono; Muhammad Akib; F.X. Sumarja; Ahmad Irzal Fardiansyah (Universitas Negeri Semarang, 2025)
This research addresses the deficiencies in the scholarly exploration of constitutional law in relation to elitist populism within the legislative framework of Indonesia. The article examines the tendency of elitist populism in Indonesian legislative practice and advocates the idea of curbing it by constitutional law. Elitist populism, in the context of this article, refers to a political approach in which leaders claim to represent the common people, while simultaneously engaging in elitist practices. This study uses a normative juridical research method using statutory and conceptual approaches, and analyzes controversial cases with significant legislation impact. The research findings show that elitist populism in legislative practice is manifested in rapid legislation, and the consolidation of power that minimizes participation fails to reflect public aspirations. To limit these tendencies, constitutional law arrangements in institutional design, supervisory mechanisms, as well as spaces for public participation and awareness, need to be stronger. Therefore, it is recommended to strengthen the institutional rules of the constitutional court, revitalize the supervisory function of the house of representatives, encourage lawmaker’s consistency in the application of meaningful participation, and build public awareness.